The Role of Management on Methods of Utilizing Information and Technology In Improving The Quality of Elementary School Teachers In Gowa District: PERAN MANAJEMEN TERHADAP METODE PEMANFAATAN INFORMASI DAN TEKNOLOGI DALAM PENINGKATAN KUALITAS GURU SEKOLAH DASAR DI KABUPATEN GOWA - Ibrahim, Mardiana (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
A The role of management on the method of utilizing information and technology in improving the quality of elementary school teachers in Gowa District. This study aims to determine how the role of management in the method of utilizing information and technology in improving the quality of elementary school teachers in Gowa Regency. The analysis method used in this study is data that is analyzed descriptively. The data analysis used in this study is qualitative analysis. Field data are reduced to obtain a firm picture of the focus of the research and remove unnecessary things and organize the data so that conclusions can be made, and this process runs continuously throughout the implementation of the research. Data obtained directly from observations, interviews, documentation or reports The population in this study is primary school teachers in Gowa District. The sample in this study was teachers with a service period of 15 years. The sampling technique is carried out randomly. This type of research is a survey research. The results of the analysis of this study on improving the quality of teachers are certainly very related to utilizing information and technology facilities in order to create a better expected and reliable performance where management is the process of planning, organizing, leadership, and controlling all organizational resources to achieve set goals or management of a result in order to achieve goals through the activities of others, it is certainly not surprising that management capabilities A good one can produce an expected goal achievement as well as the method or method used is effective and efficient, then automatically the results will also be very satisfying and of course very supported by the use of information and technology that suits the needs as reliable educators because of their abilities and qualities